ANALYSIS OF 200 CONSECUTIVE CASES OF LAPAROSCOPIC CHOLECYSTECTOMY IN A SINGLE UNIT AT A TERTIARY CARE HOSPITAL: Cases of Laparoscopic Cholecystectomy - Afzal, Surg Cdre Muhammad; Zafar, Muhammad Rafiq; Rehman, Shafqat; Khalid, Tooba; Afshan, Gul (Pakistan Armed Forces Medical Journal, 2012)
Objectives: To evaluate the results of the first 200 consecutive laparoscopic cholecystectomies by a single consultant / unit at a tertiary care hospital. Design: Quasi-experimental Place and Duration of Study: PNS Shifa Karachi, Pakistan from Nov 2009 to Oct 2011 Patients and Methods: In this prospective study, a consultant surgeon performed his first 200 laparoscopic cholecystectomies (LC) consecutively for symptomatic gallstones irrespective of status of gallbladder. During this period, 12 open cholecystectomies were carried out and patients with choledocholithiasis were excluded from study. Data including sex, age, indications for LC, conversion to open cholecystectomy, reasons for conversion, co-morbidity, types of complication, length of hospital stay and 30-day mortality was recorded. Result: There were 200 patients with symptomatic gallstones who underwent laparoscopic cholecystectomy. Female to male ratio was 5.9:1. The mean age was 44.28±13.38 years. Out of 200 patients 69% patients had chronic cholecystitis / biliary colic, 26.5% patients were with acute cholecystitis and 4.5% patients had diagnosis of empyema gallbladder. The mean operative time was 38.77 ± 13.73 min. Mean hospital stay was 1.2 days (range 1–6 days). Conversion rate to open surgery was 1.5%. Complications included cystic duct leakage in 0.5% patient, intraoperative bleeding in 1% patients, postoperative bleeding in 1% patients, sub hepatic biloma in 0.5% patient, port site infection in 3.5% patients, umbilical hernia in 0.5% patient and one patient presented with keloid at the umbilical port. Conclusion: Laparoscopic cholecystectomy is a reliable and safe treatment modality for symptomatic gallstones. Both rate of conversion and complications are reduced with growing experience of surgeon in laparoscopic technique.